Procesos de comunicación de saberes ancestrales de la cultura panzaleo en la comunidad Chilla Chico - Chicaiza Tocte, Luis Hernán (2020)
This research was developed as a communicative process of an indigenous community and as a fundamental element. It was to know the teaching methods used by older adults for the communication of ancestral knowledge in agriculture, clothing, gastronomy, music, and language, which are taught by parents and grandparents who share certain cultural features. The objective of this work was to identify the communication processes of the ancestral knowledge of the Panzaleo culture in the Chilla Chico community; to diagnose young adults and new generations about ancestral knowledge and changes in cultural elements. The purpose of this study is to identify ancestral knowledge, especially to know who are the fundamental characters that transmit this knowledge for every generation. On the other hand, we will determine if young people are interested in acquiring and maintaining the cultural identity of the community. The methodology used the Qualitative approach, and the study was carried out with the modality of fieldwork, making use of semi-structured interviews that were applied in four generations, where the information could be obtained from the analysis of results and approaches of conclusions of traditions, customs, and cultural identity. As part of the documentation, a documentary was made, which contains interviews, experiences, and stories in the different areas of community life.